Shaking table tests for the experimental verification of the effectiveness of an automated modal parameter monitoring system for existing bridges in seismic areas. Issue 7 (11th April 2018) - Rainieri, C.; Gargaro, D.; Fabbrocino, G.; Maddaloni, G.; Di Sarno, L.; Prota, A.; Manfredi, G.
Summary: Reinforced concrete bridges represent a majority of the Italian stock and they play a primary role to ensure the efficiency of the transportation network and prompt rescue in the case of an emergency. However, most of them have been designed and built according to outdated codes, or even without any seismic detailing. The significant impact of strong motions on the road network as well as the human life and economy emphasizes the need for effective strategies for post‐earthquake emergency management and to support rescue operations. The present paper aims at evaluating, against real data, the effectiveness of automated modal parameter monitoring for vibration‐based Structural Health Monitoring (SHM) of existing bridges in earthquake prone areas. This objective has been pursued in the context of shaking table tests on a 1:3 scale single span bridge representative of existing highway bridges built in the 60's in Italy. The dynamic response of the structure before and after the application of asynchronous seismic input has been analyzed for damage detection and performance assessment. Results show that partially hidden damage can be remotely detected, thus validating the interesting applicative perspectives of automated output‐only modal identification and modal‐based damage detection for fast assessment of existing bridges in the early earthquake aftershock. The robustness of the SHM system to sensor overload due to earthquake shaking has been also assessed, demonstrating the applicability of modal‐based SHM in seismic regions even in the absence of a measurement chain specifically designed to resolve the large amplitude vibrations induced by earthquakes. Finally, the possibility of complementing modal‐based SHM with drift‐based estimates is explored.